1996
DOI: 10.1007/bf02473237
|View full text |Cite
|
Sign up to set email alerts
|

Selective colocalization of lipid peroxidation and protein thiol loss in chemically induced hepatic preneoplastic lesions: the role of γ-glutamyltranspeptidase activity

Abstract: A number of studies indicate that cell proliferation can be modulated by changes in the redox balance of (soluble and protein) cellular thiols. Free radical processes, including lipid peroxidation (LPO), can affect such a balance, and a role for LPO in multistage carcinogenesis has been envisaged. The present study was aimed to assess the relationships between the protein thiol redox status and the LPO process in chemically induced preneoplastic tissue. The Solt-Farber's initiation-promotion model of chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…34 Earlier work in immunohistochemical and enzyme histochemical studies on γ-GTP in rat liver has been used during 3-me-DAB hepatocarcinogenesis. 35 Pompella et al 36 showed the decreased levels of protein thiols in GGTpositive nodules induced by chemical carcinogenesis in the rat liver. These findings correlate with the results of this study, showing elevated levels of γ-GTP in liver tumors induced by BHC.…”
Section: Discussionmentioning
confidence: 99%
“…34 Earlier work in immunohistochemical and enzyme histochemical studies on γ-GTP in rat liver has been used during 3-me-DAB hepatocarcinogenesis. 35 Pompella et al 36 showed the decreased levels of protein thiols in GGTpositive nodules induced by chemical carcinogenesis in the rat liver. These findings correlate with the results of this study, showing elevated levels of γ-GTP in liver tumors induced by BHC.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies evidenced the prooxidant action potentially played by GGT reexpressed in chemically-induced preneoplastic lesions of rat liver. When fresh cryostat sections of liver were exposed to GSH, chelated Fe(III) and glycyl-glycine, the GGT activity present in transformed cells was able to catalyze the initiation of a lipid peroxidation process, which could be revealed by means of histochemical reactions [22,23]. Experiments showed that transferrin could serve as a source of redox-active iron.…”
Section: Gsh/ggt-dependent Lipid Peroxidationmentioning
confidence: 99%
“…In this respect, recent studies from our laboratory and others have shown that another source of cellular basal production of oxidants is represented by g-glutamyl transpeptidase (GGT), 2 the plasma membranebound ectoactivity that, in a number of cell types, is in charge of metabolizing extracellular reduced glutathione (GSH). In fact, it has recently been documented that GGT activity can give rise to redox reactions, due to the interplay of reactive thiol metabolites of GSH (cysteinyl-glycine in the first place) with transition metal ions; these reactions were shown to induce the production of reactive oxygen species and lipid peroxidation (15)(16)(17)(18).…”
mentioning
confidence: 99%